Performance of Reinforced Concrete Beam with Polystyrene Blocks at Various Regions - Lim Yong Tat (Widyagama University of Malang, 2020)
Lightweight materials, such as polystyrene, can be embedded in reinforced concrete (RC) beams to reduce its weight. However, this may, to some extent, affect the performance of the structure. This research investigates the behaviour of the lightweight beams under load and determines the best position of polystyrene blocks in beams. Nine specimens with a size of 175 mm x 300 mm x 1600 mm were tested under four-point load test. The number and position of polystyrene blocks in the beams were varied. The specimens were evaluated for effectiveness in terms of effective strength to weight ratio (s-w ratio). The lightweight beam was effective when the polystyrene blocks were placed at the neutral and tensile region, offering an s-w ratio of greater than 1. The beam lost 3.8% strength with 8.4% reduction of weight.